Therapeutic angiogenesis of adipose-derived stem cells for ischemic diseases - Lina Zhao; Takerra Johnson; Dong Liu (Stem Cell Research & Therapy, 2017)
Abstract Ischemic diseases, the leading cause of disability and death, are caused by the stenosis or obstruction of arterioles/capillaries that is not compensated for by vessel dilatation or collateral circulation. Angiogenesis is a complex process leading to new blood vessel formation and is triggered by ischemic conditions. Adequate angiogenesis, as a compensatory mechanism in response to ischemia, may increase oxygen and nutrient supplies to tissues and protect their function. Therapeutic angiogenesis has been the most promising therapy for treating ischemic diseases. In recent years, stem cell transplantation has been recognized as a new technique with therapeutic angiogenic effects on ischemic diseases. Adipose-derived stem cells, characterized by their ease of acquisition, high yields, proliferative growth, and low immunogenicity, are an ideal cell source. In this review, the characterization of adipose-derived stem cells and the role of angiogenesis in ischemic attack are summarized. The angiogenic effects of adipose-derived stem cells are discussed from the perspectives of in-vitro, in-vivo, and clinical trial studies for the treatment of ischemic diseases, including ischemic cardiac, cerebral, and peripheral vascular diseases and wound healing. The microvesicles/exosomes released from adipose-derived stem cells are also presented as a novel therapeutic prospect for treating ischemic diseases.